Implementasi Strategi Pengembangan Penguatan Fungsi Pelayanan Kesehatan Hewan Dalam Meningkatkan Capaian Vaksinasi Rabies Di Kabupaten Ciamis - Intan Widianingrum (Pusat Riset dan Inovasi Nasional, 2023)
accomplishments of rabies vaccination is still not optimal yet. Meanwhile, the current situation is faced in an environment that apparently still has a low level of awareness and other environmental challenges, which is the opening of traffic lanes for RTA that becomes the risks or potential for entry of disease. Furthermore, the intensity of close relation with cats that almost every house keeps and the habit of hunting moro dogs that are routinely carried out. To solve the problem above, with a strategic management approach, Dinas Peternakan dan Perikanan Kabupaten Ciamis makes some changes and improvements in the organization. Implementation of the strategy is related to the development strategy of strengthening the function of animal health services which is expected to raise the awareness of animal-owning society to be willing to vaccinate their pets with their own will which shall indirectly protect themselves from rabies transmission. The implementation of the strategies related to the activities carried out by Dinas Perternakan dan Perikanan in the efforts to objectify the program of Pengendalian Rabies menuju Indonesai Bebas Rabies 2030 or to maintain Ciamis Zero Rabies. The output of this study is the accomplishment of rabies vaccination rate increases in line with the increased public awareness. This study uses the J. David Hunger and Thomas L. Wheelen’s theory (1996:9) which are 4 basic elements of the strategic management process and by classifying the strategies according to Kotten's theory (1991) explains several strategies and their implementation in the effort of increasing the accomplishment of rabies vaccination rate, so based on the results of the interview, observation and data processing indicates that there has been an increase in the accomplishment of rabies vaccination rate.